Edukasi dan Pelatihan Pengelolaan Sampah berbasis Bank Sampah di Desa Sukarahayu Kecamatan Tambelang - Istianah Setyaningsih; Eka Putri Yudilestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Managing waste remains a significant issue in various areas, including Sukarahayu Village, Tambelang Sub-district, Bekasi Regency. The community’s ongoing improper disposal habits, such as littering and open burning, continue to threaten both public health and the environment. This community engagement initiative seeks to increase residents’ knowledge, awareness, and involvement in waste management through education and training utilizing the waste bank model. The approach comprised three primary phases: preparation, socialization, and implementation. In the implementation phase, residents were educated about sorting organic and inorganic waste following the 3R principles (Reduce, Reuse, Recycle), the environmental and health dangers of burning waste, and received training in waste handling through the establishment of a Waste Bank Unit (WBU). The outcomes demonstrate improved community understanding of effective waste management and the creation of a waste bank management team in Sukarahayu Village. This initiative is anticipated to foster positive behavioral changes in waste handling, decrease the amount of waste sent to landfills, and deliver ongoing economic benefits to the community.